1998
DOI: 10.1091/mbc.9.6.1379
|View full text |Cite
|
Sign up to set email alerts
|

RhoG GTPase Controls a Pathway That Independently Activates Rac1 and Cdc42Hs

Abstract: RhoG is a member of the Rho family of GTPases that shares 72% and 62% sequence identity with Rac1 and Cdc42Hs, respectively. We have expressed mutant RhoG proteins fused to the green fluorescent protein and analyzed subsequent changes in cell surface morphology and modifications of cytoskeletal structures. In rat and mouse fibroblasts, green fluorescent protein chimera and endogenous RhoG proteins colocalize according to a tubular cytoplasmic pattern, with perinuclear accumulation and local concentration at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
151
2
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 67 publications
14
151
2
1
Order By: Relevance
“…The answer to these questions will require identi®cation of the extracellular signals that stimulate TC10, as well as the use of dominant negative GTPases to determine whether the function of one GTPase is dependent on the activation of another. At this time, the possibility of a cascade incorporating TC10, at least in regard to ®lopodial induction, seems likely since the ability of yet another family member, RhoG, to stimulate ®lopodial and lamellipodial formation requires CDC42 and Rac, respectively (Gauthier-Rouviere et al, 1998). On the other hand, the inability of TC10 to induce lamellipodia or stress ®bers, both in our assay and in a similar assay with Swiss 3T3 cells (Neudauer et al, 1998), suggests that Rac may not be downstream of TC10 in a cascade regulating cytoskeletal rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to these questions will require identi®cation of the extracellular signals that stimulate TC10, as well as the use of dominant negative GTPases to determine whether the function of one GTPase is dependent on the activation of another. At this time, the possibility of a cascade incorporating TC10, at least in regard to ®lopodial induction, seems likely since the ability of yet another family member, RhoG, to stimulate ®lopodial and lamellipodial formation requires CDC42 and Rac, respectively (Gauthier-Rouviere et al, 1998). On the other hand, the inability of TC10 to induce lamellipodia or stress ®bers, both in our assay and in a similar assay with Swiss 3T3 cells (Neudauer et al, 1998), suggests that Rac may not be downstream of TC10 in a cascade regulating cytoskeletal rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…A functional correlation between microtubules and Rho activity could also be drawn from studies on another exchange factor, TrioGEF that activates RhoG [52]. RhoG is an activator of Rac and Cdc42 that can promote membrane protrusion [53]. Neither RhoG nor TrioGEF binds directly to microtubules, but their activities on Rac-and Cdc42-dependent protrusion and localization to the cell periphery are dependent on an intact microtubule network [53].…”
Section: Rho Regulation Of Microtubulesmentioning
confidence: 99%
“…RhoG is an activator of Rac and Cdc42 that can promote membrane protrusion [53]. Neither RhoG nor TrioGEF binds directly to microtubules, but their activities on Rac-and Cdc42-dependent protrusion and localization to the cell periphery are dependent on an intact microtubule network [53]. This might imply that microtubule motors provide a link between Rac, Cdc42 and Rho and/or their activating GEFs and microtubules to transport activated Rho proteins to protrusions.…”
Section: Rho Regulation Of Microtubulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensile strain decreased the amount of membrane associated Rho GTPase by 70%. Other workers have shown there is a functional relationship between both Rho GTP'ase, GEF protein, and microtubules that requires an intact microtubule cytoskeleton [52,54,55]. The fact that both proteins lost their localisation to the cell periphery upon microtubule depolymerisation suggested that a microtubule dependent transport process was involved [52,54,55].…”
Section: Discussionmentioning
confidence: 99%